Chatting to learn in synchronous WhatsApp group discussion - Paramasivam, Shamala (Universiti Putra Malaysia Press, 2021)
Group discussion is a key feature in education. Despite its importance, however, its potential in higher education is under-researched. With the advent of technology in education and the vision for 21st century learning, innovative use of mobile-based technologies has become a necessity in teaching and learning. Having to get on the bandwagon, the present study examines WhatsApp as a tool for synchronous group discussion in class and how it could promote communication and learning among undergraduates. The app is used in a blended delivery design to teach a content course called Discourse Analysis in an undergraduate program for Applied Linguistics. The research is qualitative in nature and employs pragmatics as the approach to discourse analysis. The study showed that WhatsApp group discussion helped student understanding of content knowledge, facilitated group learning, and promoted learner autonomy and learner cooperation. The students used one another as resources and made sense of the course content together based on their subject matter knowledge and life experiences. They pooled their knowledge and experiences and helped each other figure out the concepts, theories and issues through a negotiation of meaning that involved active participation in the form of questions and responses that justify, explain and clarify meanings. In this new age of digital literacy, the study shows how WhatsApp synchronous group discussion can encourage cumulative learning as a way to learn content knowledge, stimulate exploratory talk as a relevant communication skill for academia and work, and promote among learners, a sense for autonomy and cooperation.